Good muslim bad muslim America, the cold war , and the roots of terror - "Mamdani, Mahmood" (New York, 2004)
In this brilliant look at the rise of political Islam, the distinguished political scientist and anthropologist Mahmood Mamdani brings his expertise and insight to bear on a question many Americans have been asking since 9/11: how did this happen? Good Muslim, Bad Muslim is a provocative and important book that will profoundly change our understanding both of Islamist politics and the way America is perceived in the world today.
Keywords: Culturalism-Islam